Wacana Pangruat Dalam Teks Cempaka Gadang - I Wayan Artayasa (Program Magister Linguistik Universitas Udayana, 2017)
This paper is a study pangruat on Cempaka Gadang manuscript. Cempaka Gadang manuscript is categorized in to verbal manuscript (tutur). It describes the ritual of cleansing of purifying. Pangruat is closely to the ritual of purifying the bad spirit of the ancestor to get a brighter way and to bring harmony to the universe. The pangruat discourse in Cempaka Gadang manuscript provides descriptions of (1) the use of pangruat to purify self and humans spiritual, (2) the use of pangruat to bring harmony to nature, (3) the use of pangruat for neutralizing bhuta characteristics. The meaning analysis of pangruat in Cempaka Gadang manuscript involves (1) as the remover of humans bad, (2) as a remover of the bad in nature, (3) to bring the natural harmony back, and (4) to redeem the sins.